2022
DOI: 10.1002/ijc.33978
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric males receiving hematopoietic stem cell transplant lose their male disadvantage in disease risk after the procedure: A retrospective observational study

Abstract: Sex differences play a relevant role in cancer susceptibility, incidence and survival.Exploring such differences is difficult because of the close interplay of genetic, epigenetic and hormonal factors. However, a better understanding of the role of such disparities in cancer mechanisms could improve its prevention and therapy. Our study explores how sex differences in pediatric outcomes vary after undergoing first and advanced-line therapy for hematological malignancies. The primary goal was to evaluate if sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A further potential explanation for the disappearance of the sex difference in the HSCT group could be found in the theory that the HSCT and its previous conditioning regimen could flatten the hormonal differences between males and females for a certain period, reducing the influence of sex on transplant-related outcomes, as some studies suggest [57]. According to this thesis, it would be possible to witness an equalization in the incidence of clinical situations that would otherwise be influenced by sex.…”
Section: Discussionmentioning
confidence: 97%
“…A further potential explanation for the disappearance of the sex difference in the HSCT group could be found in the theory that the HSCT and its previous conditioning regimen could flatten the hormonal differences between males and females for a certain period, reducing the influence of sex on transplant-related outcomes, as some studies suggest [57]. According to this thesis, it would be possible to witness an equalization in the incidence of clinical situations that would otherwise be influenced by sex.…”
Section: Discussionmentioning
confidence: 97%
“…Most studies exploring the risk factors for HCC development are based on observational studies and clinical experience. However, the major disadvantage of an observational study is that its validity is threatened by confounding by indication ( De Nardi et al, 2022 ). Furthermore, studies have shown that genetic factors may also independently modulate HCC risk ( Shimokawa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for higher cancer risk in men are not fully perceptible but probably react more exposure to cancer-causing environmental, occupational and biological risk factors. Sex differences in endogenous hormones and immune function may also play a significant role in different cancers ( De Nardi et al, 2022 ). In the current cancer treatment, chemotherapy is still the dominant treatment strategy ( Network, 2012 ).…”
Section: Introductionmentioning
confidence: 99%